Restitution Arrangements for Children Who are Economically and/or Sexually Exploited Based on Principles of Justice - Purba, Melana; Mangesti, Yovita Arie (Jurnal Hukum dan Keadilan, 2024)
This article examines the implementation of the right to restitution for child victims of economic and sexual exploitation. The goal is to assess how effectively the right to restitution is fulfilled for such victims, based on the analysis of Decision No. 331/Pid.Sus/2021/PN Yyk. It is a normative legal study with a prescriptive focus, utilizing both primary and secondary legal sources. The method of legal material collection involves a literature review with a case approach. The analysis is conducted using the syllogistic method and a deductive reasoning process. The findings reveal that the child victim received a restitution payment of Rp. 81,650,000. The decision by the Yogyakarta District Court, however, lacks clear legal certainty, as the charges presented before the trial were confirmed to be valid and compelling for the judge in reaching his decision. The judgment also reflects a sense of justice, as it addresses the victim's needs, including medical and psychological care, through a criminal decision that mandates compensation for the child victim.